PENDIDIKAN ANTI KORUPSI UNTUK GENERASI MUDA - Jacynta Shalehafilah; Devina Mayra Purnama; M Dhika Adrian; Rasid Hidayat; Sri Rizka Novi Anggraeni M; dhafin riyasy Ishak (Fakultas Hukum Universitas Djuanda, 2022)
This article is entitled Anti-Corruption Education for the Young Generation, the younger generation can have anti-corruption properties, where corruption is a dangerous disease in our beloved homeland, the impact of this corruption is very large, because of that corruption is also categorized as Extra Ordinary Crimes, the impact is not only to the public, but also to the existing system in the government, broadly speaking we instill anti-corruption values in this article, as well as anti-corruption prevention methods such as education, and cultivating an anti- corruption mindset itself, we allrealize that corruption cases in Indonesia there are so many, in fact almost every day and every moment of corruption cases appear on the surface of our homeland, setting an inappropriate punishment is a feature of the breakdown of our government system, where all of it must be revised, and also the punishment for corruptors should be the most severe among the crimes committed. others, in order to create a deterrent effect and, prevent our young generation from committing acts of corruption.